Legitimasi Hukum Pemberlakuan Syari’at Islam di Aceh: Tinjauan Yuridis, Sosiologis dan Filosofis - M Jafar (Ulumuna, 2015)
The glory of Aceh Darussalam Kingdom in the past cannot be separated from the complete application of Islamic Sharia (kāffah) as the way of life in Aceh. Reflecting the historical past, the implementation of Sharia in Aceh in the present context is absolutely necessary. However, today's enforcement must refer to the three foundations, namely judicial, sociological, and philosophical. The most fundamental of juridical basis is the Constitution of 1945 (UUD 1945) Chapter XI on Religion and paragraph 2 of Article 29, new amendment of Article 18A paragraph 1 and Article 18B paragraph 1. The implementing of Sharia law in Aceh began with the birth law No. 44/1999 regarding the Implementation Features Special of Aceh Province, then refined by law No. 18/2001 on Special Autonomy for Aceh Province as Nanggroe Aceh Darussalam province. Then it is continued by the Law Number 11/2006 on the Governing of Aceh (UUPA). The sociological ground is majority Muslim of Acehnese can receive all the products based on Islamic Sharia law. The philosophical foundation, Islamic law, should be enforced based on the Qur'an and Hadith recommended preserving religion, life, property, lineage, and resourceful. DOI: http://dx.doi.org/10.20414/ujis.v19i1.1250